2020
DOI: 10.1177/1943387520902881
|View full text |Cite
|
Sign up to set email alerts
|

Condylar Fractures: An Argument for Conservative Treatment

Abstract: Introduction: The treatment of mandibular condyle fractures remains a controversial topic in maxillofacial surgery. No uniform treatment protocol is currently available. Purpose: We performed a retrospective monocentric cohort study of patients with condylar fractures and their treatment, including long-term follow-up by telephone, followed by a short review of the literature. Patients and Methods: The available data on condylar fractures presenting at Leuven University Hospitals between January 1, 2009, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(41 reference statements)
1
2
0
3
Order By: Relevance
“…As we go more forward this window raise. This surgical window is better when compared to the retromandibular approach (control group) thus resulting in smoother manipulation, less retraction, better viewing of facial branches thus good isolation and protection during dissection, concerning this advantage we share other authors conclusions (38)(39)(40) as well as (37).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As we go more forward this window raise. This surgical window is better when compared to the retromandibular approach (control group) thus resulting in smoother manipulation, less retraction, better viewing of facial branches thus good isolation and protection during dissection, concerning this advantage we share other authors conclusions (38)(39)(40) as well as (37).…”
Section: Discussionsupporting
confidence: 59%
“…Regarding scar; good aesthetic outcome of scar was found in all patients of the control group; 9(70%) cases had visible but thin and linear scar and 1(10%) case had wide scar at 3 and 6 months, in this group all patient were satisfied by their scar and this correspondent with (Fleix and Singh 2020) (35) while (Parihar et al 2019) (3) noticed five cases developed hypertrophic scarring. In this study/study group; we only had one case of transient facial paralysis, which could be attributed to the postgraduated clinician experience, and the small sample size, (Mohamad 2011, Khan and Sayed 2022) (36,37) encountered some cases of transient facial paralysis resulted from practising this approach.…”
Section: Discussionmentioning
confidence: 97%
“…Vanpoecke et al reported that 28 of 84 patients had mouth opening widths of less than 40 mm at 3 months after injury with conservative treatment alone 23) . Guerrero et al described in their meta-analysis that the mean mouth opening width with conservative treatment alone was 41.6 mm and that with ORIF was 41.4 mm 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Переломи нижньої щелепи (НЩ) є одними з найбільш частих і складних видів травматичних пошкоджень щелепно-лицевої ділянки в дітей і становлять 18-66% від загальної кількості переломів кісток обличчя [2,7]. Серед яких переломи НЩ у ділянці виросткових відростків зустрічаються в 25-40% випадків [1,9].…”
Section: вступunclassified